Estimation of total harmonic distortion in short chorded induction motors using artificial neural network - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
In this paper, Artificial Neural Network (ANN) technique has been used for the estimation of voltage THD (Total Harmonic Distortion), current THD and power factor, mainly from input and output measurements of five different chorded induction motors fed from a pulse width modulation inverter voltage supply. A sinusoidal pulse-width modulation (SPWM) inverter feeding five different chorded three-phase induction motors were tested up to first thirty harmonic voltage component at different loads. The results show that the artificial neural network model produces reliable estimates of voltage THD, current THD and power factor.
Keywords: artificial neural network; total harmonic distortion; harmonic estimation; induction motors